Increased 1-year survival and discharge to independent living in overweight hip fracture patients. (3rd March 2016) - Flodin, Lena; Laurin, Agnes; Lökk, Johan; Cederholm, Tommy; Hedström, Margareta
Abstract : Background and purpose — Hip fracture patients usually have low body mass index (BMI), and suffer further postoperative catabolism. How BMI relates to outcome in relatively healthy hip fracture patients is not well investigated. We investigated the association between BMI, survival, and independent living 1 year postoperatively. Patients and methods — This prospective multicenter study involved 843 patients with a hip fracture (mean age 82 (SD 7) years, 73% women), without severe cognitive impairment and living independently before admission. We investigated the relationship between BMI and both 1-year mortality and ability to return to independent living. Results — Patients with BMI > 26 had a lower mortality rate than those with BMI < 22 and those with BMI 22–26 (6%, 16%, and 18% respectively; p = 0.006). The odds ratio (OR) for 1-year survival in the group with BMI > 26 was 2.6 (95% CI: 1.2–5.5) after adjustment for age, sex, and physical status. Patients with BMI > 26 were also more likely to return to independent living after the hip fracture (OR = 2.6, 95% CI: 1.4–5.0). Patients with BMI < 22 had similar mortality and a similar likelihood of independent living to those with BMI 22–26. Interpretation — In this selected group of patients with hip fracture, the overweight and obese patients (BMI > 26) had a higher survival rate at 1 year, and returned to independent living to a higher degree than those of normal (healthy) weight. The obesity paradox and the recommendations for optimal BMI need further consideration in patients with hip fracture.